Prevalence of blood parasite in dairy cattle around Keningau area, Sabah - Marimuthu, Murugaiyah; Sambrani, Freska; Yeo, Boon Kiat (2015)
A survey was conducted in and around Keningau area, Sabah to determine the incidence of blood parasites in dairy cattle. The sampling technique used was the two stage cluster sampling method. Parasitological blood examinations, packed cell volume and presence of motile parasites were recorded from the dairy cows. The overall prevalence of blood parasites in the dairy cattle was 14.98% (49 out of 327 animals were positive for blood parasites). The common blood parasites seen in the blood smears were Babesia spp. 0.31%, Anaplasma spp. infection 2.75% and microfilaria infection (4.89%). The highest percentage of blood parasite found was Theileria spp. infection (7.03%). There was significant difference (p<0.05) between the packed cell volume and presence of infections. This study revealed that the prevalence of blood parasites among the dairy cattle population in and around Keningau area were low. Based on the present study a surveillance protocol was developed for the dairy cattle in and around Keningau area, Sabah.